Effect of number of branches on the performance of fractal impeller in a stirred tank: mixing and hydrodynamics - Mule, Gunwant M.; Lohia, Rajat; Kulkarni, Amol A. (Chemical Engineering Research & Design, 2016)
Number of blades of an impeller, impeller design and its positioning in a stirred tank is known to affect the mixing in a stirred tank reactor. The extent of non-uniformity in mixing from conventional impellers can be reduced significantly using a space-filling impeller like a fractal impeller. In this work, we report the effect of number of branches (and hence the number of blades) of fractal impeller on power consumption, mixing and hydrodynamics. Velocity measurements were carried out using ultrasonic velocity profiler (UVP). Measurements showed that the performance of fractal impeller with different configuration is equivalent, however, better than standard impellers in terms of mixing achieved per unit power consumption. No significant difference was observed in radial and axial mean velocity profiles for three different configurations. However, the tangential velocity was found higher for four branches than two and three branches FL Two distinct circulation loops were observed in upper as well as lower half of the vessel in r-z plane. Strong tangential flow throughout the baffled vessel helps to achieve good mixing even at low rotational speeds. (C) 2016 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Fractal impeller; Number of branches; UVP; Tangential velocity; Mixing

Mixing of medium viscosity liquids in a stirred tank with fractal impeller - Mule, Gunwant M.; Kulkarni, Amol A. (Theoretical Foundations of Chemical Engineering, 2016)
Mixing of viscous liquids in a stirred tank is a daunting task. The present paper explores the possibility of using a fractal impeller for mixing of viscous liquids in a stirred tank. The analysis includes power consumptions characteristics, mixing characteristics and the flow patterns in the stirred tank. Ultrasonic velocity profiler (UVP) was used to measure the local velocities in the stirred tank. Fractal impeller found to exhibit different power consumption characteristics than known for conventional impellers. For the range of viscosities 0.58-0.192 Pa s, mixing time found to be directly proportional to the power consumption per unit mass. The normalised mean radial velocity profiles were found to be independent of fluid viscosities studied in the present work.

Effect of object shape on the flow past microstructures in small channel - Mule, Gunwant M.; Kulkarni, Amol A. (Fluid Dynamics Research, 2021)
Flow past objects in microfluidics and microscale devices are used to perturb the flow and thereby achieve effective mixing and heat transfer. This paper presents the observations on the flow past bluff (elliptical, rectangular and triangular) cylindrical micropillars (objects) having different cross-sectional area in a micro-channel through 2D simulations. The pertinent range of Re based on object dimension (0.1 Re 150) was chosen to understand the wake dynamics that would remain relevant for comparison with literature data. Drag coefficient, recirculation region, critical Reynolds number for flow oscillations and vortex strength in a channel were studied. The drag coefficient was found to increase with aspect ratio of the object. The critical Re for flow oscillations was found to increase with the cross-sectional area of the object. The vortex strength in a channel was seen highest for triangular cylinder compared to elliptical and rectangular cylinder.
Keywords: 2D simulations; flow past objects; micro and mini-channels; micropillars; wake dynamics